Assessment of Severity of Anemia Among Children Under 5 Years - obaid, Khamees; Ma’ala, Eqbal (Iraqi National Journal of Nursing Specialties, 2013)
Objective(s): The aim of this study was to assess the severity of anemia among children under 5 years and to find out relationship between severity of anemia in children with socio-demographic variables such as: child gender, age, supplement diet, hookworm, pica, parent’s education level, father’s and mother’s occupation, and family monthly income with severity of anemia Methodology: A descriptive cross sectional study was conducted at the primary health care centers in Alsadr city for the period of 1 st July 2011 to the 1st November 2011.Non probability (purposive) sample of (630) children who aged under 5 years and who attended to primary health care centers of Alsadr city. The data were collected through using special constructed questionnaire designed, which comprises two parts. Part one consists of child’s demographic characteristics and their families filled by using interview technique and part of two consist hemoglobin level. The reliability of the questionnaire was determined through a pilot study and the validity through a panel of experts. The data were analyzed through the application of descriptive statistic frequency, percentage, and the application of inferential statistical procedures, which multiple logistic regressions Results: The results of the study indicated that (69%) of children have anemia in general, and (35%) of them have moderate anemia, (31%) of them have mild anemia and (3%) of them have severe anemia. The results of the study indicated there is significant relationship between severity of anemia with supplement diet, pica, mother’s education and family monthly income. Moreover, there is no significant association between severity of anemia in children and (child’s gender, child’s age, infection worms, father’s education level, parents’ occupation. Recommendations: The researchers recommend the application of screening program for anemia and determine the severity of anemia, especially children under 5 years and increase community awareness about the dangers of anemia especially sever of anemia in children